2012
DOI: 10.1080/1941126x.2012.684333
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Usage Patterns Recorded between an Electronic Reference and an Electronic Monograph Collection: The Differences in Searches and Full-Text Content Viewings

Abstract: This paper presents the results from a quantitative and systematic analysis comparing the online usage of an e-reference and an e-monograph collection. A very strong relationship exists between size and usage: the larger the collection, the greater the usage. An equally strong relationship exists between searches and viewings, meaning that the more there are searches performed, the more will full-text content be viewed. The smaller e-reference collection has also seen significantly greater use proportional to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Because it has been demonstrated that e-books of a monographic nature are used very differently from electronic reference books, usage were examined separately (Lamothe, 2012). Only e-monograph data were examined in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Because it has been demonstrated that e-books of a monographic nature are used very differently from electronic reference books, usage were examined separately (Lamothe, 2012). Only e-monograph data were examined in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2007, the number of viewings recorded for NetLibrary books at Laurentian University had dropped by 52 percent whereas individually purchased titles on MyiLibrary experienced nearly a 1000 percent increase in viewings over the same period of time. Added to this, Lamothe (2012) reported a steady drop in “viewings per e‐book” ratio value for NetLibrary titles. And in a previous 2010 study, Kimball et al (2010) noted some concern with the currency of the content of their NetLibrary collection, which had been stagnating since 2005.…”
Section: Resultsmentioning
confidence: 89%
“…Usage from electronic reference titles was not included whatsoever. Since patrons will use electronic reference books differently compared to electronic monographs (Lamothe, 2012, 2010), distinguishing usage between the two types of e‐books is important because combining usage from one type to the other might skewer overall results (Staiger, 2012). For this reason and for the sake of simplicity, the term “e‐book” will be used to represent e‐monographs from this point onward.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported clear differences in e-reference and e-monographs use by patrons (Corlett-Rivera and Hackman, 2014;Lamothe, 2013c;Lamothe, 2012). Performing a quantitative comparison on e-reference usage would answer several questions.…”
Section: Introductionmentioning
confidence: 99%
“…E-reference have been demonstrated to record higher levels of usage compared to their e-monograph counterparts, mostly because library patrons seem to feel more comfortable using them rather than their print equivalent (Husted and Czechowski, 2012;King, 2012;Lamothe, 2012;Reid et al, 2006). Corlett-Rivera and Hackman (2014) found that students and faculty at the University of Maryland heavily favored e-reference.…”
Section: Introductionmentioning
confidence: 99%